Hubungan antara Work Life Balance dan Kepuasan Kerja pada Karyawan di PT PLN PERSERO Area Ambon - Maryo Wildo Wenno (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2018)
Every organization expects every employee to have a high level of job satisfaction. This study aimed to see the relationship between work life balance and job satisfaction by using quantitative methods with product moment correlation technique from Carl Pearson. Hypothesis in this research was a positive and significant correlation between work life balance and job satisfaction. Measuring tool used in this research was work life balance scale by Hayman (2005) with result of reliability test was 0.774 and job satisfaction scale by Spector (1997) with result of reliability test was 0.942. The sample of this research was employees at PT PLN Ambon Area. From product moment correlation analysis obtained r value = 0.337 with significance 0.001 (p <0.05). The result of statistical analysis obtained showed that there was a positive and significant relationship between work life balance and job satisfaction at employees in PT PLN Persero Ambon Area.